The Role of Cyberpsychology in the Context of Digital Marketing - Dewani, Shinta Laura; Presida, Sesy Briliana; Swatantra, Gallant Yosava (Klabat Journal of Management, 2024)
The widespread use of the internet and digital technology is revolutionizing consumer interactions with the business world. This necessitates marketers to grasp how psychological factors influence behavior in the virtual realm, a facet that can be explored through the field of cyberpsychology. Cyberpsychology offers insights into human interactions with the digital world, paving the way for personalized marketing content and a profound understanding of consumer preferences. This study aims to elucidate the role of cyberpsychology in the context of digital marketing, providing additional insights into efforts to optimize business strategies in the digital realm. The research employs a literature review method sourced from online platforms. The results indicate that a deep understanding of the relationship between cyberpsychology and digital marketing has unveiled the complexity of human interactions in the digital sphere, the dynamics of consumer behavior, and the pivotal role of color psychology and design in crafting successful digital marketing campaigns. The implications of these findings can offer valuable guidance for marketers to enhance consumer engagement, comprehend market preferences, and devise more effective marketing strategies amidst the evolving challenges of the digital era.